In vitro screening of commercial sorghum hybrids and omega-3 supplementation in Holstein steers - Thorn, Ross Lee (Kansas State University, 2024)
Sorghum hybrids were evaluated for their susceptibility to both in vitro and in situ microbial digestion. Sorghum hybrids were sourced from institutional and commercial sources and 39 hybrids were evaluated. Grains were analyzed using near-infrared spectroscopy (NIR) to estimate each grain’s protein and starch content using an Perten DA 7250 spectrometer (Perten Instruments, Springfield, IL, USA). Grains were split into subsamples and processed by grinding, reconstitution followed by ensiling (RE), and steam-flaking. Each processed grain was used as substrate and was combined with a buffered ruminal fluid solution, before being capped with an Ankom IR gas measuring device (Ankom Technology, Macedon, NY). In vitro cultures using ground sorghum as substrate were incubated for 28.25 hours, whereas in vitro cultures using RE and SF grain were allowed to incubate for 30 hours. Cumulative gas production, volatile fatty acids concentrations from in vitro cultures, and in vitro dry matter disappearance were measured and used to assess how well microbes digested each grain. In situ dry matter disappearance (ISDMD) was measured for ground and RE processed grain to provide an additional assessment of ruminal microbial digestion of the grain. In vitro gas production data were analyzed using non-linear models to estimate four gas production parameters: maximum cumulative gas production (K), time to reach half of the cumulative gas production (t[subscript 1/2]), rate of gas production (r) , and maximum rate of gas production (m). Methane yield was estimated from each in vitro culture, using the VFA concentrations from the in vitro cultures solution using the formula Methane Yield (g/kg DM) = 4.08×(Acetate (mol/100 mol)/Propionate (mol/100 mol) + 7.05 (Williams et al., 2019). Each grain’s estimated protein and starch content were correlated to K, t[subscript 1/2], r, m, VFA concentrations from in vitro cultures, methane yield, IVDMD and ISDMD. Starch and protein content correlated with K, m, and methane yield in ground sorghum. Starch and protein content also correlated with m and ISDMD in RE sorghum, while starch and protein content correlated with K in steam-flaked sorghum. These results indicated that there was a noteworthy variation in susceptibilities of sorghum grain to in vitro microbial digestion; however, more extensive processing of the grain (RE or steam-flaking) decreased the differences among the grain with respect to in vitro microbial digestion. A backgrounding study using an extruded blend of flaxseed and microalgae product (FAB; greatOplus), was fed to 11 ruminally and duodenally fistulated Holstein steers to assess ruminal microbial modification of the fatty acids present in FAB, as well as their post-ruminal disappearance. Steers were housed in a facility equipped with an Insentec feed and water monitoring system (Hokofarm;, Emmeloord, the Netherlands). A cross over design was utilized and treatments consisted of a control diet without the FAB and a treatment diet with FAB included at 10% of the diet dry matter. Dry matter intake by day was different (P<0.001); steers consuming the FAB had greater feed intakes on day 2, 6 and 7 compared to the steers fed the control diet. Water consumption was not different (P>0.10). Ruminal acetate concentrations were not different between treatments (P>0.10). Ruminal propionate concentrations were affected by hour (P=0.026); steers fed the FAB supplement, had greater ruminal propionate concentrations at hour 8 (P<0.05) and tended to have greater propionate concentrations at hour 0 (0.05<P<0.10). Ruminal butyrate concentrations were also affected by hour (P=0.036); steers fed the FAB supplement tended to have greater ruminal butyrate concentrations at hours 8 and 10 (0.05<P<0.10). Steers fed the control diet had greater ruminal butyrate concentrations at hours 18 and 24 than steers fed FAB (P<0.05). Ruminal pH and ammonia concentration were not different between treatments (P>0.10). Duodenal flow of several fatty acids, (g/d) were greater for steers fed the FAB and in particular, the ruminal flow of α-linolenic acid (ALA) was four times greater for steers fed the FAB supplement compared to steers fed the control diet (6.3 g/d vs 1.6 g/d; P=0.001) The coefficient of intestinal disappearance of each fatty acid was not different between treatments for the vast majority of the fatty acids (P>0.05), except for ALA. There was a reduction in the coefficient of intestinal disappearance of ALA for steers fed the FAB supplement compared to steers fed the control diet (0.64 vs 0.41; P=0.039). Feeding this FAB supplement may increase the ruminal flow of omega-3 fatty acids to the small intestine, allowing the potential for increased absorption of these essential fatty acids; however, extensive biohydrogenation will occur which leads to a small proportion of dietary omega-3 fatty acids reaching the small intestine, compared to the amount of omega-3 fatty acids in the basal diet.
Keywords: GreatOplus; In vitro; In situ; Sorghum; Omega-3; α-linolenic acid; Alpha-linolenic acid